Perancangan Aplikasi Mobile GIS Berbasis Android Untuk Informasi Wisata Di Kabupaten Solok - Resma Yanti, Tira; Sularno (Journal Of Informatics And Busisnes, 2024)
Solok District, a government areas in West Sumatra Province located at the position between 01º 20'27 "-01º 21'39" south latitude and 100º-100º 25'00' 33'43 'east longitude. Formal legally, Solok regency formed by Law No. 12 of 1956 on the Establishment of the Autonomous Region in the Regional Environmental District of West Sumatra province. At this time, Solok regency consists of 14 sub-districts, 247 villages and 6 districts. So that the number of tourists continues to increase and is not experiencing saturation of the attractions, the need for development in the field of tourism. In order to get optimal results, the development in the field of tourism is not only supported by one party but is a collaboration of various parties, including the b usiness community, traditional leaders and the government. One area that has the potential for development of tourism and the need is of Solok district. In realizing the travel strategy then made a geographic information system-based tourism districts solok web with Google Maps API. The results of this study in the form of geographic information systems Solok regency tourism web based so the tourism information can be accessed by the public with easy, fast, economical, and can be done anywhere and anytime. All such information will be interconnected with each other.